Адаптація найкращого досвіду міської логістики для українських міст (аналіз досліджень та проектів міської логістики країн ЄС) - Вороніна, Р. М. (Видавництво Львівської політехніки, 2016)
Проаналізовано досвід і найкращі практики міської логістики країн ЄС у сфері перевезення людей та вантажів. Класифіковано рішення на основі вартості відповідних проектів. У результаті аналізу запропоновано рішення у галузі міської логістики для українських міст, які передбачають заходи щодо міських вантажних перевезень та міської мобільності, а також комплексні рішення для місцевих адміністрацій. The paper describes the best practices in urban logistics of the EU cities in the transportation of people and goods The mentioned best practices are classified on the basis of their implementation costs. Key milestones of the EU research projects in logistics and supply chain management are presented, including urban logistics, global supply network coordination and collaboration, corridors, hubs and synchromodality, sustainable, safe and secure supply chains, information systems for interconnected logistics. Appropriate urban logistics solutions for Ukrainian cities are proposed which include measures for urban freight transport and urban mobility, as well as recomendations for local administrations. Sustainable Urban Mobility Plans and Sustainable Urban Logistics Plans must be developed for Ukrainian cities using recommendations and best practices. Infrastructure,legislative, planning, f inancial and “soft” instruments must be used for mobility managenment and urban logistics management. Urban Consoladation Centers are regarded as a good decision for many cities but can`t be organized in Ukrainian cities nowadays.
The adaptation of urban logistics best practices for ukrainian cities
Keywords: міська логістика; міська мобільність; міські вантажні перевезення; плани сталої міської мобільності; міський логістичний центр; найкращий досвід; urban logistics; urban mobility; urban freight transport; sustainable urban mobility plans; Urban Consoladation Centers; best practices